Análise de dano em compósitos laminados utilizando modelo de falha tridimensional - Ximenes, Kayque Andson Silva (2023)
Laminate composites are materials widely used in several areas because they allow the construction of structural elements with an excellent weight/strength ratio. These materials demonstrate a fragile behavior, presenting strong anisotropy and complex failure and rupture mechanisms. This makes it difficult to characterize the non-linearity of its mechanical behavior. Thus, the main objective of this work was the implementation and application of a 3D failure criterion for laminated composites associated with progressive degradation models in a commercial software of Finite Elements. For this purpose, the Puck’s three-dimensional failure model was used, incorporated into a abrupt degradation model, Element Weakening Method (EWM), a progressive degradation model, Constant Stress Exposure Method (CSE), and a model based on Continuous Damage Mechanics (CDM). The algorithms developed in this work were implemented in the form of user subroutines for material characterization (UMAT), programmed in Fortran and incorporated into Abaqus R . It also aims to adapt the search process for the fracture angle to reduce the computational cost of the analysis. Numerical and experimental results from the literature were used to validate the model. The results were partially satisfactory as it was effective in most examples, but was lacking in the delamination approach. In addition, it demonstrated an average computational cost reduction of 23%, but only in some models, pointing to a considerable effect in the assembly of the system but not in its resolution.